Use of telehealth during COVID-19 pandemic in India: literature review - Alaka Chandak; Mrudula Holkar; Abhishek Moghe; Ketaki Washikar (International Journal of Public Health Science (IJPHS), 2023)
COVID-19 has provided an unprecedented opportunity to expand access and coverage to the country's healthcare system via telehealth. Because of the growing need for telemedicine by healthcare providers, the Medical Council of India issued Practice Guidelines in March 2020. Medical specialties like ophthalmology, dermatology, and neurology offered telehealth services during pandemics. Low-middle-income countries like India are highly dependent on out-of-pocket expenses for health services. Thus, there is a need to understand telehealth's accessibility, feasibility and affordability. This review aims to understand trends regarding the access and patient response to telehealth in India during the COVID-19 pandemic. We reviewed published papers to understand better accessibility and patient response to the healthcare delivery systems via telehealth in India. The results of this review showed that patients were satisfied with the use of telehealth. Healthcare providers and patients believe telehealth can be suitable for various healthcare services, including follow-up visits in clinical disciplines and minor health problems. In conclusion, for Telehealth to understand further, quality evidence must be available, and its role in developing integrated parts of the healthcare system to be defined.